Analisis Penyebab Maraknya Cyberbullying di Era Digital pada Remaja - Audrey Afralia; Desy Safitri; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2024)
The development of increasingly sophisticated social media has made the phenomenon of cyberbullying a serious problem in affecting adolescents' mental and emotional health. It is through these social media platforms that individuals can easily intimidate, belittle or emotionally harm others. As a result, incidents of cyberbullying are becoming more widespread and have a serious impact on adolescents' emotional and mental well-being. The purpose of this paper is to find out the causes of cyberbullying in the digital era in adolescents. The method used is literature review by collecting and taking the essence of previous research and analyzing several sources relevant to the research topic. The results of research conducted by various experts show that the causes of rampant cyberbullying in adolescents in the digital era are caused by several factors, namely anonymity online, indifference to consequences, group pressure, lack of awareness of the negative impact as well as lack of parental supervision and lack of digital literacy.